The Agility Factor: Building Adaptable Organizations for Superior Performance - Christopher G. Worley; Thomas D. Williams; Edward E. Lawler III (San Francisco, CA Jossey-Bass, 2014)
After examining more than 243 large companies across 18 industries over a thirty-year period, the authors found a handful of companies in every industry that consistently outperformed their peers. These companies successfully adapted to changes in their competitive environments. In most industries, they were not the "usual suspects" that consume column inches in the business press, but companies that quietly went about the business of delivering sustained performance. These companies possessed "agility," a dynamic organizational capability that enabled them to perceive and interpret environmental changes, test possible responses, and fully implement required changes quickly and reliably. Like all capabilities, they are difficult to build, but also difficult for competitors to replicate. Agility is a key to long-term sustained profitability and performance. This book will outline the components of agility, their foundations in good management practices, and how they combine to form a powerful system that is a source of competitive advantage.
Keywords: Organizational change; Organizational effectiveness; Management; Agile Management (HRM2072-N)